HIV: how to manage low-level viraemia in people living with HIV - Emily K Hanners; Jessica Benitez-Burke; Melissa E Badowski (BioExcel Publishing Ltd, 2022)
Background: People living with HIV (PLWH) and receiving antiretroviral therapy (ART) have a goal of achieving and maintaining viral suppression; however, low-level viraemia (LLV) (HIV-RNA viral load levels of 50-999 copies/mL) persists in certain patients despite consistent medication adherence, lack of drug interactions and no genotypic resistance. This is a narrative review of the growing evidence of LLV in PLWH to determine risk factors and ART management strategies and to discuss the implications of LLV on the development of future virological failure. Methods: A systematic, comprehensive literature search was completed in the English language using PubMed, Google Scholar and bibliography review to gather information about LLV in PLWH between July 2014 and June 2021. The following keywords were used as search terms: "low-level viremia", "HIV", "viral blip", "intensification", "genotyping", "adherence" and "resistance." Results: Of 66 studies examined, 39 were analysed and included in this review. All trials included were published between 2014 and 2021. Eleven studies assessed risk factors for LLV. Identified risk factors were low CD4+ T cell nadir counts at baseline, higher baseline viral load measurements, medication non-adherence, non-nucleoside reverse transcriptase inhibitor use and others. Three studies assessed genotyping and concluded that the interpretation of both historical RNA genotype resistance testing and current proviral DNA genotype resistance testing in patients with LLV is appropriate. Seven studies were evaluated and determined that modifying or intensifying ART regimens resulted in decreased incidence of virological failure. Conclusion: This compilation of reviewed data gives a framework for the management of PLWH with LLV. Currently, there are no clear or definitive treatment directions for LLV provided in guidelines. Complicating this topic further is the unclear and varying definitions of LLV. Future research is needed on this topic but patients presenting with LLV should have their medication adherence assessed, drug interactions checked and ART intensified, where appropriate.